2015
DOI: 10.1007/s11249-015-0587-1
|View full text |Cite
|
Sign up to set email alerts
|

The Positron Probe Microanalyser Studies of Defect Distribution Induced by Machining of Copper, Iron and Titanium

Abstract: We demonstrate the application of the new experimental technique: positron probe microanalyser for studies of the defect profiles induced by milling. Metal foils of Cu, Fe and Ti were subjected to machining in a milling machine with different cutting speed. This technique revealed well-defined profiles of defects below the machined surface which was extended up to hundreds of micrometres. The extent of the profile depended on the metal and the cutting speed. The positron probe microanalyser allowed us to trace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The maximum, at the depth of about 50 µm ( Figure 7 ), is a new interesting feature which was not observed in distributions registered for copper exposed to other treatment processes [ 16 , 17 ]. For analysis of the near surface region the depth up to 100 µm was additionally presented in Figure 9 .…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…The maximum, at the depth of about 50 µm ( Figure 7 ), is a new interesting feature which was not observed in distributions registered for copper exposed to other treatment processes [ 16 , 17 ]. For analysis of the near surface region the depth up to 100 µm was additionally presented in Figure 9 .…”
Section: Resultsmentioning
confidence: 81%
“…In turn, the exponential character can be assigned to the rest of profiles. The former tendency was registered in machined copper [ 16 ], while the latter was noted in copper samples exposed to sliding and cutting [ 17 ]. Various types of S parameter distributions from one treatment process were also obtained for austenitic stainless steel exposed to sliding under varied dry load conditions [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that PAS can be used for the detection of machining damage in Ti-6Al-4V (Patton et al), copper (Dryzek et al, 2015) and stainless steel (Horodek et al, 2012). The ability to distinguish between damaged an undamaged samples was attributed to the increased number of dislocations in the near-surface, caused by deformation during machining.…”
Section: Positron Annihilation Spectroscopymentioning
confidence: 99%